Legal Enforcement Model in The Eradication of Trawls Capture As an Efforts To Meet SDG's 14: Blue Economy Case Study in Bengkulu - Tri Andika; Deli Waryenti; Patricia Ekowati Suryaningsih (Faculty of Law, Universitas Jenderal Soedirman, 2022)
One of the goals of Sustainable Development is to protect and preserve the oceans, and the natural resources within them, which are known as the Blue Economy concept. Along the way, sustainable development in the management of fishery resources in Indonesia faces problems. This problem arose from the inconsistency of the trawling prohibition policy which ended in the prohibiting of fishing vessels to use trawls in the Indonesian Fishing Territory based on the Regulation of the Minister of Maritime Affairs and Fisheries Number 18/PERMEN-KP/2021 articel 7. In Bengkulu City, the implementation of the ministerial regulation has been carried out with the transfer of fishing gear, but fishermen who use trawls still use trawls. Based on the results of previous research, it was found that in Bengkulu City to date there are 100 boats using trawling fishing gear with the potential for conflict between fishermen getting wider. The research method used in this study is an empirical juridical research method with the desired outcome is the right model in law enforcement against the use of trawls in Bengkulu City. The ideal model in regulating trawling fishing gear is policy consistency by prohibiting trawling in fishing areas that are harmful to their use both in marine ecosystems and economically, socially and culturally by fishermen in each region. Keywords: Models, Enforcement, Law, Trawls, SDGs 14.